Advanced Cancer Patients' Understanding and Perceptions of Phase I Clinical Trials. (26th November 2015) - Pawlowski, Jamie; Malik, Laeeq; Mahalingam, Devalingam
Abstract : This questionnaire-based study assessed the understanding and perceptions of cancer patients who were participating in a Phase I clinical trial at baseline and determined any changes after enrollment. Thirty-six patients participated. Less than one-third of respondents (28.5%) thought the purpose of Phase I trials was dose escalation for safety and efficacy. Patients anticipated varying degree of therapeutic benefit ranging from stable disease (47.1%) to complete shrinkage of the tumor (32.4%). No change in measured themes was observed. Patients participating in Phase I trials need further education to improve their understanding of the true intent of early Phase trials.